An investigation of strategies used in alcohol brand marketing and alcohol-related health promotion on Facebook. (29th April 2016) - Lim, Megan SC; Hare, James D; Carrotte, Elise R; Dietze, Paul M
Objective: Alcohol brands are incorporating social networking sites (SNS) into their marketing programmes. SNS are also being used to reduce alcohol consumption and harms by health promotion organisations. Marketing via SNS can attempt to influence consumers using a range of strategies from traditional marketing, social media, and behaviour change theory. This study systematically quantifies marketing strategies used by alcohol brands and health promoters on Facebook. Methods: We identified the 10 most popular alcohol brands and health promotion organisations in Australia on Facebook and extracted all posts from April 2014. A framework was developed, listing 33 SNS marketing strategies. The frequency of use of each strategy in posts was counted for all profiles. Results: The median number of fans of alcohol brands was 189, 290 compared with 7562 for health promotion pages. A total of 210 Facebook posts were analysed. Popular marketing strategies included visual attraction, connecting with other organisations, and links to culture and events. Time-specific and day-specific posts and tweets were used more regularly by alcohol brands than health promotion agencies. Conclusions: Alcohol brands remain substantially more popular than health promotion organisations, and this difference is likely driven by offline factors rather than specific use of marketing strategies. However, health promotion organisations can learn from the strategies used by popular brands, particularly in the use of time and day-specific content.